Research on the influence of spindle temperature rise of drilling and tapping machine on machining accuracy. Issue 2 (April 2021) - Yu, Lianzhou; Xing, Zhihui; Gao, Mingming; Shang, Li
Abstract: With the progress of science and technology, the improvement of product performance, as well as the improvement of user's requirements for product experience, the accuracy of machine tools and equipment is required to be higher and higher. Spindle is an important component of high-speed drilling and tapping machine. The change of its temperature directly affects the accuracy of machining size and appearance of machine equipment. This paper mainly studies the causes of spindle temperature rise and the methods to prevent excessive temperature rise.